2020
DOI: 10.1002/ca.23585
|View full text |Cite
|
Sign up to set email alerts
|

Secular evolution of femoral morphology from a clinical perspective

Abstract: IntroductionIntramedullary nailing is the surgical method of choice for the treatment of proximal femur or femoral shaft fractures. Implant manufacturers aim to design implants fitting for the broadest possible population segment. As complete morphological data sets of long bones are not widely available, anatomical collections of historical dry bone specimens may represent abundant additional sources of morphological three‐dimensional (3D) data for implant design, provided they are consistent with present pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
0
6
1
Order By: Relevance
“…In a study of Buller et al, a negative correlation was found between age and FNI [13]. Schmutz et al have shown a statistically significant relationship between age and FNA angles [4]. In contrast to these study results, we observed no statistically significant correlation in terms of age -FNA (r = -0.082, p = 0.53) and age -FNI (r = -0.098, p = 0.45).…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…In a study of Buller et al, a negative correlation was found between age and FNI [13]. Schmutz et al have shown a statistically significant relationship between age and FNA angles [4]. In contrast to these study results, we observed no statistically significant correlation in terms of age -FNA (r = -0.082, p = 0.53) and age -FNI (r = -0.098, p = 0.45).…”
Section: Discussioncontrasting
confidence: 95%
“…Understanding the racial differences in the native 3D femoral anatomy is important for an accurate preoperative planning and designing more compatible orthopedic implants [1,6,7]. In the literature, there are many studies that investigate the femoral anatomical features of different populations [1][2][3][4][5]7,10]. Most of these studies, that analyzed the racial differences on anatomical features, have focused on the Caucasian population from western countries [2][3][4][5]; however, the studies investigating the native femoral anatomy of the populations originated from different races on 3D models are limited [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations